Hubungan Dukungan Suami dan Budaya Dengan Pemilihan Tempat Persalinan - Yeni Aryani; Islaeni Islaeni (SEAJOM: The Southeast Asia Journal of Midwifery, 2018)
Birth assistance in health facilities is one of the most effective ways to reduce maternal mortality. The skilled birth attendants can provide prompt and appropriate services in case of complications for the mother and baby. For this purpose, midwives should disseminate appropriate information so that the mother can have birth in the health facility. The objective of this study was to determine the relationship of husband and cultural support to the choice of birth place in the working area of Berseri Pangkalan Kerinci Health Center of Palalawan District. This retrospective study used a quantitative approach with a total sample of 87 respondents selected with cluster sampling technique. Data were obtained through questionnaires. The data analysis used univariate and bivariate with chi-square statistic test. There was a relationship of a husband's support to the choice of birth place and with a p value of 0.000 and there was a relationship of culture to the choice of birth place with a p value of 0.028. Therefore, the health personnel should disseminate and improve P4K programs to optimize community participation in the preparation of childbirth, including a choice of birth place.